New guidelines on radiation survey and sanitary assessment of residential, public and industrial buildings and facilities in terms of radiation safety indicators. Part 2 - D. V. Kononenko; T. A. Kormanovskaya; A. S. Vasilyev; K. A. Saprykin (Радиационная гигиена)
The paper (in two parts) presents an overview of the new guidelines MR 2.6.1.0333-23 (approved on 01 December 2023) that supersede guidelines MU 2.6.1.2838-11, which were used for organizing radiation surveys of residential, public and industrial buildings and facilities and their sanitary assessment in terms of radiation safety indicators over the past 12 years. Due to a large number of critical comments on the document received during this period, a need for significant revision emerged. The scope of the revised document was expanded, and now it covers all stages of the life cycle of buildings and facilities: commissioning; operation period; overhaul and reconstruction; demolition. In the second part of the paper, numerous innovations are considered in terms of estimating the indoor average annual equilibrium equivalent concentration of radon isotopes. The reasons for the introduction of certain changes are outlined. Based on the results of previous studies and the review of foreign recommendations, the procedures for measuring indoor radon concentrations have been improved in such a way as to balance the increase in the reliability of estimating the average annual equilibrium equivalent concentration of radon isotopes and the increase in time and labor costs for testing laboratories to conduct the survey. The revised document introduces separate procedures for measuring indoor radon concentrations in new buildings and existing buildings with round-the-clock and non-round-the-clock occupancy. Estimating a weighted average based on the results of two-season measurements will represent a significant step forward in assessing the actual average annual radon concentrations in operated buildings in Russia. At the same time, the case of radiation survey of the buildings within the framework of events with legally limited duration is considered separately in the revised document. Taken together, the changes should have a positive impact on the quality of measurement information obtained by testing laboratories and underlying decisions made by executive authorities.